Refining decisions on which primary care patients to screen for glaucoma - Wick, Bruce; Gall, Ronald (Canadian Journal of Optometry, 2009)
Introduction: Glaucoma, which is often accompanied by elevated intraocular pressure (IOP), causes progressive optic nerve atrophy and blindness. Among ocular structure parameters abnormalities in central corneal thickness (CCT), cup-to-disc (C/D) ratio, inter-eye C/D ratio asymmetry, optic disc area, and neuro-retinal rim area (N-RRA) appear to be highly correlated with glaucoma. We compare these specific ocular structures in a group of young normal pre-presbyopic patients and in a group of patients being treated for glaucoma. Methods: After written informed consent, 1433 consecutive normal, and 56 consecutive patients being treated for glaucoma were assessed by including age, race, sex, IOP (NCT), C/D ratio, optic disc area, N-RRA (Optos), central center thickness (CCT), and anterior chamber depth. Results: Combinations of findings in CCT, C/D ratio, C/D ratio asymmetry, disc area, and N-RRA (assessed by Z-score) were present in 65.52% of patients being treated for glaucoma and 22.96% of young normal patients. For young normal patients, overall average CCT was 550.37+/-39.47µm. Overall average C/D ratio was 0.39+/-0.11. Inter-eye C/D asymmetry was 0.02+/-0.06. Overall average disc area was 2.46+/-0.49mm2 (7863.54+/1630.42 pixels). Overall average N-RRA was 1.44+/-0.35mm2 (4785.88+/1161.14 pixels). C/D ratio increased modestly with disc area increase, an increase not associated with thinning N-RRA. Thin N-RRA was associated with small optic discs that had large C/D (t=-8.21, p=0.000, DF=93). There was a significant difference between young normal patients and patients being treated for glaucoma in CCT, C/D ratio, C/D ratio asymmetry, disc area, and N-RRA. Conclusion: More than one in five (22.96%) young normal patients has ocular structure findings similar to those found in patients being treated for glaucoma. These results will help refine decisions on which primary eye care patient to screen for glaucoma.